Powstanie sądów apelacyjnych w 1990 r. na przykładzie Sądu Apelacyjnego w Białymstoku - Fiedorczyk, Piotr (Czasopismo Prawno-Historyczne, 2026)
The article presents the circumstances of the establishment of the Court of Appeal in Białystok in 1990. It is one of the ten Courts of Appeal established at that time. The Court was established in connection with the major systemic transformation that took place in Poland after 1989, following the fall of the communist system. The purpose of establishing the Court was to reduce the Supreme Court’s workload and to shorten the duration of court proceedings. The establishment of the Court in Białystok was the result of a broad campaign by local communities, which saw the establishment of the Court as an opportunity for Białystok’s civilisational advancement. One of the arguments in favour of creating the Court was the existence of the Faculty of Law in Białystok, which was expected to provide a staffing base for the new institution. The thirty-six years of operation of the Court of Appeal in Białystok to date have confirmed that the decision to establish it was justified. They have also confirmed the correctness of the decision to return to the three-instance model (appeal, cassation) of court proceedings, as it existed until 1950, and replaced the two-instance communist model (revision).